Creating doorways: finding meaning and growth through art therapy in the face of life-threatening illness. (September 2021) - Reilly, R.C.; Lee, V.; Laux, K.; Robitaille, A.
Abstract: Objectives: This article presents the findings of a pilot study situated in a tertiary care cancer centre and examines the impact of an art therapy group on the experiences of women living through breast cancer. Study design: The study design used in this study is a qualitative cross-case comparative case. Methods: Ten women were interviewed about their experiences making art, many for the first time. Interviews were transcribed and analysed, along with the participants' artist statements. Results: Categories include the following: the significant benefits of art therapy on their sense of self-efficacy; the emotionally enhancing nature of making art for the first time; the power of their artwork to trigger insights about themselves (including subcategories of self-actualization, existential growth, and post-traumatic growth) or in communicating their experiences to loved ones; and how making art changed their worldview and life philosophies, creating doorways of possibilities. Conclusion: This study suggests that art therapy provides a safe context to reflect on profound personal changes and to re-story losses following adversity through creative practices as a dimension of care. Graphical abstract: Image 1